2016
DOI: 10.2217/fon-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Urothelial Bladder Cancer: Impact of Regimen and Variant Histology

Abstract: NACT was associated with improved survival, pCR and pDS. Furthermore, responses to NACT were not dependent on presence of VH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…In a subgroup analysis from the randomized controlled trial (RCT) SWOG 8710, patients with mixed histology (squamous or glandular) were seen to have a survival benefit with NAC (HR 0.46; 95% CI 0.25-0.87; p = 0.02) compared with primary RC [14]. These results are consistent with the findings of Kaimakliotis et al [15] who reported similar oncological outcomes of NAC for patients with pure urothelial bladder cancer (n = 54) and variant histology (n = 30), with the latter being mostly represented by squamous or glandular differentiation. The presence of squamous or glandular variants was associated with higher rates of pathological downstaging (OR 4.01; 95% CI 1.16-13.9) but similar OS when compared with pure urothelial carcinomas [16].…”
Section: Pathological Classificationsupporting
confidence: 85%
“…In a subgroup analysis from the randomized controlled trial (RCT) SWOG 8710, patients with mixed histology (squamous or glandular) were seen to have a survival benefit with NAC (HR 0.46; 95% CI 0.25-0.87; p = 0.02) compared with primary RC [14]. These results are consistent with the findings of Kaimakliotis et al [15] who reported similar oncological outcomes of NAC for patients with pure urothelial bladder cancer (n = 54) and variant histology (n = 30), with the latter being mostly represented by squamous or glandular differentiation. The presence of squamous or glandular variants was associated with higher rates of pathological downstaging (OR 4.01; 95% CI 1.16-13.9) but similar OS when compared with pure urothelial carcinomas [16].…”
Section: Pathological Classificationsupporting
confidence: 85%
“…The presence of variant histology does not appear to compromise the efficacy of preoperative chemotherapy in patients with UC of squamous or glandular differentiation. 8 , 9 However, the utility of preoperative chemotherapy for patients with PUC remains poorly defined. Anti-programmed cell death 1 (anti-PD1)/programmed cell death ligand 1 (PDL1) immune checkpoint inhibitors (ICIs) are also used to treat patients with UC 10 13 and have an emerging role in preoperative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic complete response was reported in ten studies (4-6,8,10-14,36) while pathologic downstaging was reported in nine studies (4,5,7,8,10,11,(13)(14)(15). S u r v i v a l b e n e f i t w i t h N A C i n V H o f U C w a s demonstrated in two studies (5,14), and specifically with sarcomatoid differentiation (11) and squamous differentiation (6,9).…”
Section: Actual Resultsmentioning
confidence: 99%